68Ga-FAPI-PET/CT improves diagnostic staging and radiotherapy planning of adenoid cystic carcinomas: imaging analysis and histological validation - Röhrich, Manuel; Syed, Mustafa; Liew, Dawn P.; Giesel, Frederik L.; Liermann, Jakob; Choyke, Peter L.; Wefers, Annika K.; Ritz, Thomas; Szymbara, Marina; Schillings, Lisa; Heger, Ulrike; Rathke, Hendrik; et al. (Radiotherapy and oncology, 2021)
Background - Adenoid cystic carcinomas (ACCs) are rare epithelial tumors mostly situated in the head and neck region and characterized by infiltrative growth. The tumor stroma of ACCs includes cancer-associated fibroblasts (CAFs) expressing Fibroblast Activation Protein (FAP), a new target for positron emission tomography (PET) imaging. Here we describe the value of PET/ computed tomography (PET/CT) imaging using 68Ga-labelled FAP-Inhibitors (68Ga-FAPI-PET/CT) and their clinical potential for staging and radiotherapy planning in 12 ACC patients (7 primary, 5 recurrent). - Patients and methods - Patients underwent contrast enhanced staging CT (ceCT) and magnetic resonance imaging (ceMRI) before 68Ga-FAPI - PET/CT. PET-scans were acquired 10, 60 and 180 minutes after administration of 150-250 MBq of 68Ga-labelled FAPI tracers. SUVmax and SUVmean values of ACCs and healthy organs were obtained using a 60% of maximum iso-contour. FAP and alpha smooth muscle actin (α-SMA) immunohistochemistry was performed in 13 cases (3 with and 10 without 68Ga FAPI-PET/CT). Staging and radiotherapy planning based on 68Ga-FAPI-PET/CT versus ceCT/MRI alone were compared. - Results - We observed elevated tracer uptake in all ACCs. Immunohistochemistry showed FAP-expressing CAFs in the tumor. Compared to conventional staging, 68Ga-FAPI-PET/CT led to upstaging in 2/12 patients and to detection of additional metastases in 3 patients, thus in total 42% of patients had their staging altered. Moreover, 68Ga-FAPI PET improved the accuracy of target volume delineation for radiotherapy, as compared to CT and MRI. - Conclusion - 68Ga-FAPI-PET/CT is a promising imaging modality for ACC, increasing the accuracy of staging exams and radiotherapy planning volumes, as compared conventional to CT and MRI.